Assistant General Practitioner Training Bases in Hebei Province: the Assessment and Recommendations for Improvement - Min ZHANG, Shibin SONG, Shujun LI, Jinjia ZHANG, Weiguo QIAN, Zhishan ZHOU, Rongying WANG (Zhongguo quanke yixue, 2022)
Background As an important supplement for strengthening the development of general practitioners (GPs) workforce in primary care in China's rural areas, the training for assistant GPs has been carried out in Hebei Province for five consecutive years. Standardizing the construction of the bases for training assistant GPs, and ensuring the quality of the training are key measures to improve the quality of primary care services in Hebei rural areas. Objective To understand the assessment of Hebei's assistant GP training bases in 2020, and put forward policy suggestions targeting the existing problems. Methods We conducted this study during July 27 to 31, 2020. We assessed the 23 assistant GP training bases in Hebei using the Assistant General Practitioner Training Base Assessment System developed by the Chinese Medical Doctor Association, involving general condition, training management, faculty team, process management, quality control and supporting measures. We also conducted a questionnaire survey with trainees randomly selected from these bases (two or three trainees chosen from each base) for understanding their socio-demographics, understanding of the training, satisfaction with the training, attitudes on the career prospect of an assistant GP, and level of intention to work in rural areas. Results The rates of qualified, basically qualified and unqualified bases were 65.2% (15/23) , 34.8% (8/23) , and 0, respectively. Thirteen 13 bases (56.5%) had not yet set up an independent general medicine department; 11 bases (47.8%) had qualified teaching rounds assessed in terms of number and implementation standards; 10 bases (43.5%) carried out small lectures and case discussions appropriately assessed in terms of number and implementation standards. The rate of passing the national Assistant Physician Licensing Examination once was≥85% in 2019 for trainees in 8 bases (34.8%) . The rate of passing the completion examination at the end of the training conducted for the first time in all bases in 2019 was≥85% for trainees in 12 bases (52.2%) . A total of 50 trainees attended the questionnaire survey. The prevalence of being satisfied with the design of the rotation of departments, training contents, clinical training base, primary care practice base, and the teaching team was 90.0% (45/50) , 90.0% (45/50) , 92.0% (46/50) , 86.0% (43/50) , and 94.0% (47/50) , respectively. The career prospect of an assistant GP was thought to be good by 39 trainees (78.0%) . Twenty-six trainees (52.0%) were willing to practice in rural areas. The level of satisfaction with policies related to the training for assistant GPs or primary care practice bases differed significantly by age in trainees regardless of whether the bases were qualified or basically qualified (P<0.05) . Conclusion In general, Hebei's training bases for assistant GPs were found with a low rate of setting an independent general medicine department, unsatisfactory training quality, and low trainee satisfaction. It is suggested that these training bases should strengthen the establishment of a general medicine department and connotation construction of general practice, improve the construction of primary care practice bases, standardize the process management, thereby improving the training quality.